D-Chiro-Inositol Regulates Insulin Signaling in Human Adipocytes - Montt-Guevara, Maria Magdalena; Finiguerra, Michele; Marzi, Ilaria; Fidecicchi, Tiziana; Ferrari, Amerigo; Genazzani, Alessandro D.; Simoncini, Tommaso (Frontiers in Endocrinology, 2021)
D-Chiro-Inositol (D-Chiro-Ins) is a secondary messenger in the insulin signaling pathway. D-Chiro-Ins modulates insulin secretion, the mitochondrial respiratory chain, and glycogen storage. Due to these actions D-Chiro-Ins has been proposed to correct defective insulin function in a variety of conditions characterized by metabolic dysfunction, such as polycystic ovary syndrome (PCOS), obesity, gestational diabetes and fat accumulation at menopause. Since it is unclear whether D-Chiro-Ins directly acts on adipocytes, we aimed to study D-Chiro-Ins’s actions on adipocyte viability, proliferation, differentiation, and insulin-related protein expression using a human adipocyte cell line derived from Simpson-Golabi-Behmel Syndrome (SGBS) which fully differentiates to mature adipocytes. Throughout differentiation, cells were treated with D-Chiro-Ins, 17β-estradiol (E2) or Insulin. Cell viability and proliferation were not affected by D-Chiro-Ins, then D-Chiro-Ins promoted cell differentiation only during the final days of the process, while E2 enhanced it from the first phases. D-Chiro-Ins stimulated lipid storage and the production of big lipid droplets, thus reducing the content of free fatty acids. We also found that D-Chiro-Ins, either alone or in combination with insulin and E2 increased the expression and activation of insulin receptor substrate-1 (IRS1) and glucose transporter type 4 (GLUT4). In conclusion, this work shows that D-Chiro-Ins plays a direct role in the differentiation and in the function of human adipocytes, where it synergizes with insulin and estrogen through the recruitment of signal transduction pathways involved in lipid and glucose storage. These findings give clear insights to better understand the actions of D-Chiro-Ins on fat metabolism in women in physiology and in a variety of diseases.